Nacionalni jeziki v EU: med pravno zavarovano vrednoto in oviro za delovanje enotnega trga - Hojnik, Janja (Slavia Centralis, 2020)
National Languages in the EU: between the legally protected value and an obstacle to the functioning of the single marketThe purpose of this paper is to demonstrate how EU law, in particular through the case law of the EU Court of Justice, solves cases of conflict between the single market of the EU, which constitutes a fundamental aim of the EU, and the efforts of the Member States to maintain different languages, which constitute an obstacle to the functioning of the single market. The impact of the EU market in particular on the use of language in the sale of goods (either in terms of labels on the products displayed in stores, either in the advertising of the goods in stores and in the media) is pointed out. Moreover, the problem of language in the context of freedom of movement of workers, including the issue of the use of the original name in other EU Member States, is emphasised. Finally, the landmine problem of the common currency impact on the linguistic diversity of the Member States is discussed.
Keywords: multilingualism; internal market; EU; free movement of goods; EU citizens; personal name; euro